Indolactam Alkaloids: Syntheses and Emerging Therapeutic Applications - MacQueen, Jordan; Billingsley, Kelvin L. (Synlett, 2025)
Protein kinase C (PKC) enzymes play critical regulatory roles in maintaining cellular homeostasis. In turn, specific isoforms have emerged as targets for therapeutic intervention, and recent studies have highlighted the importance of PKC activation in preventing cancer cell proliferation. The indolactam alkaloids are a family of natural products that potently activate conventional and novel PKC isozymes. Importantly, this activity offers new opportunities for drug design and the development of novel chemotherapeutics. In this review, we describe our recent synthetic studies aimed at accessing numerous members of this natural product family. We also detail various approaches to prepare focused libraries of indolactam-based analogues. These efforts have facilitated medicinal chemistry studies of the indolactam scaffold and importantly provided a preclinical platform for evaluating PKC activation as a therapeutic strategy in multiple cancer models.1 Introduction2 Total Syntheses of Indolactam Alkaloids3 Biological Studies of Indolactam Alkaloids4 Conclusions and Outlook
Keywords: alkaloids; total synthesis; medicinal chemistry; therapeutics; protein kinase C